2015
DOI: 10.5603/cj.a2015.0024
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of transcatheter aortic valve implantation on left atrial appendage function

Abstract: (Cardiol J 2015; 22, 5: 527-534)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Diastolic dysfunction, associated with impaired active relaxation, is a feature of most AS patients. Several studies showed improvement of diastolic function 6,7 including active relaxation early after AVR 8 , however, the percentage of patients with moderate to severe DD increases 10-years after AVR 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Diastolic dysfunction, associated with impaired active relaxation, is a feature of most AS patients. Several studies showed improvement of diastolic function 6,7 including active relaxation early after AVR 8 , however, the percentage of patients with moderate to severe DD increases 10-years after AVR 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, due to differences in clinical practice across centres, extrapolation of results may be of limited value. Evidence suggesting improved left atrial and left atrial appendage function after TAVR suggests that resolution of thrombus may be accelerated with anticoagulation [22]. Data regarding long-term follow-up with TOE to assess for resolution of LAT and SEC were not available, which is another limitation of the current study.…”
Section: Limitationsmentioning
confidence: 90%
“…LAA velocities improved significantly after TAVI in LFLG AS patients, but not in AS patients with other flow and gradient patterns. Recently, Serkan et al reported improvement in LAA velocities after TAVI especially in low EF and marked LV diastolic dysfunction. Our results were in line with their report.…”
Section: Discussionmentioning
confidence: 99%